1971
DOI: 10.1084/jem.133.6.1294
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Dissection of an Antigen Molecule: Specificity of Humoral and Cellular Immune Responses to Glucagon

Abstract: Bovine glucagon, a polypeptide of 29 amino acids, was immunogenic in guinea pigs. The immunologic determinants of glucagon were investigated using isolated tryptic peptides of the hormone. Antibodies from virtually all of more than two dozen animals had specificity primarily for the amino-terminal heptadecapeptide (NM) and showed little or no binding with the carboxy-terminal undeca- and dodecapeptides (C). The smallest synthetic peptide of a series initiated at residue 16 which measurably bound antibody compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

1971
1971
1983
1983

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(34 citation statements)
references
References 21 publications
4
29
1
Order By: Relevance
“…We may not conclude that our results on lysozyme coincide with the findings in glucagon (Senyk et al ., 1971). No peptide from tryptic digest of glucagon could function as an immunogen in either antibody formation or delayed -type hypersensitivity, while both peptides , PP-3 and PP-9, from peptic digest of lysozyme were immunogenic .…”
Section: Introductioncontrasting
confidence: 82%
See 2 more Smart Citations
“…We may not conclude that our results on lysozyme coincide with the findings in glucagon (Senyk et al ., 1971). No peptide from tryptic digest of glucagon could function as an immunogen in either antibody formation or delayed -type hypersensitivity, while both peptides , PP-3 and PP-9, from peptic digest of lysozyme were immunogenic .…”
Section: Introductioncontrasting
confidence: 82%
“…It has been reported that the antigenic site on a molecule recognized by immunocytes for production of humoral antibody is distinct from that for induction of delayed-type hypersensitivity with synthetic polypeptides (Schlossman, Herman and Yaron, 1969), flagellin (Ichiki and Parish, 1972) and glucagon (Senyk et al, 1971) as immunogens. The results with flagellin and its acetoacetylated derivatives as immunogens showed no serological cross reactivity 152 YOKOMURO et HOMMA Vol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showing a dissociation between antigen-induced mediator production in one cell population and proliferation in another population deserve further exploration with a common cell population (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The repeated failure of antibodies directed against soluble antigen to block T cell proliferation has led to two major hypotheses: (a) B cells and their secreted products, antibodies, recognize epitopes that differ from determinants recognized by inducer T cells (17,18); and (b) antigen processing creates new determinants that are not recognized by antibodies because of structural or conformational changes (9,19,20). We show that antibodies specific for epitopes that are not altered during processing 2 Definition of inducer cells as hapten and conjugate specific refers to specificity of activation rather than specificity of binding.…”
Section: Evidence For a Conserved Domain Of The I-a Molecule That Dirmentioning
confidence: 99%